W/HAP catalyzed terpenic alcohols oxidation: kinetic studies - Poman, Aishwarya; Kamble, Paresh; Vinod, Chathakudath P.; Rathod, Virendra; Kantam, Mannepalli Lakshmi (Reaction Chemistry & Engineering, 2025)
The selective oxidation of natural alcohols into carbonyl derivatives is a pivotal transformation in synthetic organic chemistry and industrial applications. This study focuses on the oxidation of borneol, a bicyclic secondary terpenic alcohol, into camphor using a tungsten-exchanged hydroxyapatite (W/HAP) catalyst and hydrogen peroxide as a green oxidant. Hydroxyapatite was synthesized via co-precipitation and functionalized with sodium tungstate to create the W/HAP catalyst, which was characterized using techniques such as SEM, EDS, TPD, XPS, and N2 adsorption-desorption to evaluate its surface morphology, porosity, and chemical composition. Oxidation reactions were conducted under optimized conditions, employing dimethylacetamide (DMA) as a solvent to achieve maximum conversion and selectivity. The W/HAP catalyst demonstrated superior performance, achieving nearly 99% conversion of borneol with 100% selectivity for camphor. Reaction parameters, including temperature, reactant stoichiometry, solvent choice, and catalyst loading, were systematically investigated. Higher reaction temperatures and oxidant concentrations favoured rapid conversion while maintaining high selectivity. Solvent effects revealed that DMA stabilized peroxo-tungstate intermediates, enhancing reaction efficiency compared to other solvents. Kinetic studies confirmed a first-order reaction mechanism with respect to borneol, and the activation energy was determined to be 44.23 kJ mol-1, highlighting the catalytic efficiency of W/HAP. Reusability tests confirmed the stability of the W/HAP catalyst over multiple cycles with minimal tungsten leaching. The methodology was extended to other terpenic alcohols, with varying degrees of success, emphasizing the substrate-specific activity of the catalyst. This work underscores the potential of tungsten-based heterogeneous catalysts in sustainable alcohol oxidation and highlights the industrial relevance of camphor synthesis as a renewable and eco-friendly approach to produce fine chemicals, fragrances, and pharmaceuticals.